2014
DOI: 10.1208/s12249-014-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-Controlled Release Delivery System for Hydrogen Sulfide Donor

Abstract: Abstract. Hydrogen sulfide (H 2 S) is having many potential pharmacological and physiological actions which reported that therapeutically useful concentration is low (100-160 μM) and a higher concentration could be toxic. Most of its donors produce it on coming into contact with water. All of these problems could be solved by a controlled-release delivery system which does not utilize water in any of its development steps. Therefore, 12 sustained release formulations were prepared by dissolving sodium hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…One obvious area of long-acting H 2 S donor formulations is ocular applications (glaucoma), given the fact that intraocular administration of various H 2 S donors is known to have a significant lowering effect on the intraocular pressure (Salvi et al, 2016;Huang et al, 2017). Ali et al (2014) at Teva Pharmaceuticals disclosed the preparation of a dozen sustained release H 2 S formulations (designated as "phase-sensitive smart polymer-based formulations") by dissolving NaHS in polymer solutions, prepared by dissolving polymers (consisting of either polylactide or polylactide coglycolide, containing free carboxylic acid or capped allyl ester end group) in a mixture of benzyl benzoate and benzyl alcohol. The polymers contained 0.8% w/v NaHS, had physiological osmolarity, and their pH was adjusted to 7.4.…”
Section: H 2 S-donating Polymers and Special Pharmaceutical Formentioning
confidence: 99%
See 1 more Smart Citation
“…One obvious area of long-acting H 2 S donor formulations is ocular applications (glaucoma), given the fact that intraocular administration of various H 2 S donors is known to have a significant lowering effect on the intraocular pressure (Salvi et al, 2016;Huang et al, 2017). Ali et al (2014) at Teva Pharmaceuticals disclosed the preparation of a dozen sustained release H 2 S formulations (designated as "phase-sensitive smart polymer-based formulations") by dissolving NaHS in polymer solutions, prepared by dissolving polymers (consisting of either polylactide or polylactide coglycolide, containing free carboxylic acid or capped allyl ester end group) in a mixture of benzyl benzoate and benzyl alcohol. The polymers contained 0.8% w/v NaHS, had physiological osmolarity, and their pH was adjusted to 7.4.…”
Section: H 2 S-donating Polymers and Special Pharmaceutical Formentioning
confidence: 99%
“…They had a variable degree (6%-27%) of initial H 2 S release ("burst release"), followed by a steady release of H 2 S, which was tracked over a period of 72 hours. It was concluded that controlled release of H 2 S (suitable for ocular indications where subconjunctival or subcutaneous administration would be the possible delivery routes) was achieved as a proof-of-principle by many of the disclosed formulations (Ali et al, 2014).…”
Section: H 2 S-donating Polymers and Special Pharmaceutical Formentioning
confidence: 99%
“…Just as regular drugs, H 2 S-releasing prodrugs can be administered orally ( 192 , 196 , 259 ), intraperitoneally ( 243 ), topically ( 185 ), ocularly ( 10 ), and intravenously ( 243 ). The H 2 S-releasing prodrugs that reached clinical trials—ATB-346, IK-1001, GIC-1001, DBTS, and SG1002—are orally administered, with the exception of IK-1001.…”
Section: Development Status Of H 2 S Prodrugsmentioning
confidence: 99%
“…28 It has been claimed that in lower concentrations this oil is just a little irritant to the eye and does not cause any tissue damage. 29,30 BB was also applied for the development of Verisome TM which is an ocular drug delivery technology. 31…”
Section: Oil Solubility Studymentioning
confidence: 99%